Logic and elementary proving methods - Ahmad, Shamsatun Nahar; Mohamad Khalid, Rusnani; Yeng, Foo Fong (Penerbit UiTM (UiTM Press), 2025)
This book includes five chapters which aim to provide university-level students with a solid foundation in set theory, mathematical logic, and proof techniques. This edition seeks to equip students and educators with insightful, relevant information on the fundamentals of logical reasoning and introductory proof methods, accompanied by clear explanations of key concepts and principles underlying proof techniques. We hope this book provides a better understanding for students and educators in teaching and learning set theory, logic, and proving techniques.